Associations between childhood height and morphologically different variants of melanoma in adulthood. (November 2016) - Meyle, Kathrine Damm; Gamborg, Michael; Hölmich, Lisbet Rosenkrantz; Baker, Jennifer Lyn
Abstract: Aim of the study: Melanoma subtypes have different aetiological characteristics. Child height is positively associated with adult melanoma; however, a clarification of associations with specific melanoma variants is necessary for an improved understanding of risk factors underlying the histologic entities. This study investigated associations between childhood height and future development of cutaneous melanoma variants. Method: A cohort study of 316, 193 individuals from the Copenhagen School Health Records Register, with measured heights at ages 7–13 years who were born from 1930 to 1989. Melanoma cases were identified via linkage to the national Danish Cancer Registry and subdivided into subtypes. Cox proportional hazards regressions were performed. Results: A total of 2223 cases of melanoma distributed as 60% superficial spreading melanoma (SSM), 27.5% melanoma not otherwise specified (NOS), 8.5% nodular melanoma (NM), and 2% lentigo maligna melanoma (LMM). The remaining rare melanoma forms were not analysed. Childhood height was positively and significantly associated with SSM, melanoma NOS, and NM, but not LMM, in adulthood. Per height z-score at age 13 years, the hazard ratios were 1.20 (95% confidence intervals [CI]: 1.13–1.27) for SSM, 1.19 (95% CI: 1.09–1.29) for melanoma NOS, and 1.21 (95% CI: 1.04–1.41) for NM. Further, growth patterns were linked to the melanoma variants with persistently tall children having an increased risk of developing SSM, melanoma NOS, or NM. Conclusion: Childhood height is positively associated with the majority of the melanoma variants. These results suggest that the underlying processes contributing to childhood height and growth patterns interconnect early-life events with the predisposition to melanomagenesis in adulthood. Highlights: Childhood height was positively and significantly associated with the majority of melanoma subtypes. Diverse growth patterns in childhood were differentially associated with future melanomagenesis. Height and melanoma risk may be linked by biological mechanisms, and these remain to be elucidated.